Psychiatry's need for Vergangenheitsbewältigung: ‘culture wars’, cognitive dissonance and coming to terms with the past - Peter Lepping; Rob Poole (BJPsych Open, 2022)
UK psychiatry's sense of self rests on being part of a socially progressive national tradition. This makes it difficult to engage with more critical narratives. The process of analysing and accepting psychiatry's past can help our profession to get closer to its real self and on a path to a better future.